Experimental criminal law: A survey of contributions from law, economics and criminology - Christoph Engel (Max Planck Institute for Research on Collective Goods, 2016)
In three distinct disciplines, crime and punishment are studied experimentally: in empirical legal studies, in experimental economics, and an experimental criminology. These three disciplines have surprisingly little interaction. The current paper surveys the rich evidence, and discusses the methodological reasons for running experiments on these issues, the limitations of the method, and how they can be mitigated.
Keywords: A12; C91; C93; D03; H26; K14; 330; crime; punishment; experiment; experimental economics; experimental criminology